Impact of impulse irrigation in different phases of the growing season on rice yield in the Krasnodar Territory. Issue 2 (December 2021) - Malysheva, N; Kizinek, S; Khadzhidi, A; Kuznetsov, E; Kravchenko, L
Abstract: The article presents a study of water consumption of rice crops during periodic irrigation in various interphase periods of the growing season. The experiments were carried out on a plot of 21.2 hectares in the rice-growing enterprise of the RBF "Krasnoarmeysky". The object of the study is an intensive variety of Rapan rice of Russian selection. The subject of the study is the water regime during the growing season of rice. It was found that the transition to intermittent irrigation during the growing season of rice "germination-tillering", "loading-flowering" and "maturation" allowed to reduce the irrigation rate by 11.4, 5.1, 1.5%, respectively, compared with traditional methods of rice irrigation. The results of harvesting rice grains showed that the average yield according to the experiment was 75.7 c/ha, which is more than in the control by 1.2 c/ha. Additional profit from increasing the yield on the experimental variants ranged from 1, 440 rubles/ha to 2, 880 rubles/ha, net profit - from 480 rubles/ha to 960 rubles/ha. The total economic effect of the introduction of the pulse irrigation mode into production in various interphase periods of rice cultivation ranged from 549.83 rubles/ha to 1490.71 rubles/ha.